Drug Survival of Anti Interleukin-17 and Interleukin -23 Agents after Adalimumab Failure in Hidradenitis Suppurativa: A Pilot Study - Federica Repetto; Gabriele Roccuzzo; Lorenza Burzi; Luca Mastorino; Paolo Dapavo; Pietro Quaglino; Simone Ribero (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)